2014
DOI: 10.1152/ajpheart.00621.2013
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum Ca2+ release is both necessary and sufficient for SK channel activation in ventricular myocytes

Abstract: SK channels are upregulated in human patients and animal models of heart failure (HF). However, their activation mechanism and function in ventricular myocytes remain poorly understood. We aim to test the hypotheses that activation of SK channels in ventricular myocytes requires Ca(2+) release from sarcoplasmic reticulum (SR) and that SK currents contribute to reducing triggered activity. SK2 channels were overexpressed in adult rat ventricular myocytes using adenovirus gene transfer. Simultaneous patch clamp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 41 publications
3
46
0
1
Order By: Relevance
“…61 We recently showed that SKCa channels overexpressed in rat ventricular myocytes are responsive to spontaneous Ca 2+ waves and can effectively diminish the amplitude of pro-arrhythmic afterdepolarizations. 29 In line with our findings, single-cell electrophysiology studies of ventricular myocytes from a chronic canine model of HF demonstrated that SKCa inhibition effectively evokes AP instability. 59 Underscoring a protective role of SKCa channels in diseased hearts, blockade of SKCa channels in rabbit failing hearts was shown to enhance predisposition to Ca 2+ -dependent triggers exacerbating arrhythmic potential.…”
Section: Skca and Ventricular Arrhythmia/hfsupporting
confidence: 88%
See 1 more Smart Citation
“…61 We recently showed that SKCa channels overexpressed in rat ventricular myocytes are responsive to spontaneous Ca 2+ waves and can effectively diminish the amplitude of pro-arrhythmic afterdepolarizations. 29 In line with our findings, single-cell electrophysiology studies of ventricular myocytes from a chronic canine model of HF demonstrated that SKCa inhibition effectively evokes AP instability. 59 Underscoring a protective role of SKCa channels in diseased hearts, blockade of SKCa channels in rabbit failing hearts was shown to enhance predisposition to Ca 2+ -dependent triggers exacerbating arrhythmic potential.…”
Section: Skca and Ventricular Arrhythmia/hfsupporting
confidence: 88%
“…28 Importantly, in cultured rat ventricular myocytes overexpressing SK2 we recently demonstrated that Ca 2+ release from the sarcoplasmic reticulum (SR) Ca 2+ channels' ryanodine receptors (RyR2 s) is not only necessary but also sufficient to evoke hyperpolarizing ISK. 29 In parallel, Mu et al showed that RyR2-mediated SR Ca 2+ release is at least in part responsible for activation of atrial plasmalemmal SKs. 30 Colocalization of SKCa channels with voltage-dependent Ca 2+ channels points to their involvement in repolarization of the action potential.…”
Section: Structure/functionmentioning
confidence: 98%
“…In cardiomyocytes, trans-sarcolemmal Ca 2+ influx through L-type Ca 2+ channels, Ca 2+ release from sarcoplasmic reticulum (SR), or combination of both, regulates the gating of SK channels (Lu et al, 2007; Terentyev et al, 2013). SK channels are coupled to L-type Ca 2+ channels, and Ca 2+ influx through L-type Ca 2+ channels directly activates SK channels (Lu et al, 2007; Maingret et al, 2008).…”
Section: The Role Of Sk Channels In Cardiomyocyte Repolarizationmentioning
confidence: 99%
“…9 SK channels have prominent impact on atrial electrophysiology, and some reports also describe functional ventricular importance under pathophysiological conditions, such as heart failure. [10][11][12][13][14] Moreover, genomewide association studies have provided evidence for common variants in the KCNN3 gene being associated with risk of atrial fibrillation (AF). [15][16][17] We and others have previously shown SK channel inhibition to be antiarrhythmic in various ex vivo and in vivo animal models of experimental AF.…”
Section: Introductionmentioning
confidence: 99%